Analisis Pengaruh Harga dan Kualitas produk Terhadap Keputusan Pembelian Konsumen pada produk krupuk di Kediri - Zuhri, Syaifudin; rahayu ningsih, Lilis sugi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In a competitive business world, price and product quality are two important factors that influence purchasing decisions. This study was conducted to determine the effect of price and product quality on consumer purchasing decisions at CV. Merpati Sejahtera Kediri. This study uses a quantitative approach with a survey method, where data is obtained by distributing questionnaires to consumers of krecek krupuk CV. Merpati Sejahtera totaling 30 respondents. The analysis technique used is multiple linier regression to test the effect between independent variables (price and product quality) on the dependent variable (purchase decisions). The results of this study indicate that both price and product quality have a positive and significant effect on consumer purchasing decisions, both partially and simultaneously. These findings indicate that competitive pricing strategies and improving product quality can be important factors in driving purchasing decisions.